The ethics of secret diplomacy: A contextual approach - Bjola, C (Taylor and Francis, 2013)
Under what conditions is secret diplomacy normatively appropriate? Drawing on pragmatic theories of political and ethical judgement, this paper argues that a three-dimensional contextual approach centred on actors' reasoning process offers an innovative and reliable analytical tool for bridging the ethical gap of secret diplomacy. Using the case of the US extraordinary rendition programme, the paper concludes that secret diplomacy is ethically unjustifiable when actors fail to invoke normatively relevant principles of justification, inappropriately apply them to the context of the case and when the actors' moral reasoning process suffers from deficient levels of critical reflection concerning the broader implications of secret engagements for diplomatic conduct.